2010
DOI: 10.1016/j.jas.2009.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of microlith implemented projectiles during the Middle and the Late Epipaleolithic of the Levant: experimental and archaeological evidence

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters. AbstractThe study comprises an experimentally based investigation of interaction between temporal change in the morphology of microlithic tools and transformations in projectile technology during the Late Pleistocene in the Levant. Archery experiments with differently designed arrows fitted with various types of microliths representing subsequent Epipaleolithic cultures of the Levant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(46 citation statements)
references
References 31 publications
5
38
0
3
Order By: Relevance
“…Pargeter's (2007) hunting experiments with 33 replicated Howiesons Poort segments, hafted in a variety of positions to produce 27 weapons, showed that they can be used successfully to hunt animals. Although not directly related to the Howiesons Poort, Yaroshevich et al (2010) conducted more recent experimental work, using transversely hafted backed artefacts closer in size to the Sibudu quartz assemblage to tip arrows than those used by Pargeter. They demonstrate that such arrows have considerable penetrating abilities, and that they have some of the highest durability indices (Yaroshevich et al, 2010).…”
Section: Current Understanding Of the Use Of Howiesons Poort Backed Tmentioning
confidence: 99%
“…Pargeter's (2007) hunting experiments with 33 replicated Howiesons Poort segments, hafted in a variety of positions to produce 27 weapons, showed that they can be used successfully to hunt animals. Although not directly related to the Howiesons Poort, Yaroshevich et al (2010) conducted more recent experimental work, using transversely hafted backed artefacts closer in size to the Sibudu quartz assemblage to tip arrows than those used by Pargeter. They demonstrate that such arrows have considerable penetrating abilities, and that they have some of the highest durability indices (Yaroshevich et al, 2010).…”
Section: Current Understanding Of the Use Of Howiesons Poort Backed Tmentioning
confidence: 99%
“…The literature on this issue has identified amply two distinct challenges: 1) identification of criteria that would distinguish a lithic armature (or "point") from other pointed artifacts, and 2) identification of the delivery technology associated with the propulsion of that armature (e.g., Ahler and McMillan, 1975; Barton and Bergman, 1982;Bergman and Newcomer, 1983;Corliss, 1972;Dockall, 1997;Evans, 1957;Fenenga, 1953;Fischer et al, 1984;Forbis, 1962;Frison, 1978;Frison et al, 1976;Holdaway, 1989;Hughes, 1998;Kay, 1996;Lombard and Pargeter, 2008;Marks, 1998;Odell, 1977Odell, , 1988Pargeter, 2007;Roper, 1979;Shea, 1988Shea, , 2006Shea et al, 2001;Shott, 1997;Thomas, 1978;Wadley and Mohapi, 2008;Witthoff, 1968;Woods, 1988;Wyckoff, 1964;Yaroshevich et al, 2010). The term "projectile" is used here in its literal sense to mean an object projected, thrown, or launched forth by force.…”
Section: Introductionmentioning
confidence: 99%
“…d 'Errico 1991;Fisher 1995;Villa and d'Errico 2001;d'Errico and Henshilwood 2007). Identification of shaping techniques and use wear (including diagnostic impact fractures) is based on comparison with experimental replication of manufacture and use (Newcomer 1974;d'Errico et al 1984;d'Errico and Backwell 2003;Villa et al 2009;Yaroshevich et al 2010), as well as previously published examples of similar artefacts (J. Deacon 1984;d'Errico and Henshilwood 2007;Bradfield and Lombard 2011;Bradfield 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A spin-off fracture can be defined as a secondary fracture originating from the surface of a bending (hinge or step terminating) fracture. These fractures occur when already broken pieces of a projectile element are pressed together as a result of kinetic energy stored in the shaft during impact with a target (Yaroshevich et al 2010); several examples of this specific type of fracture were observed on the Kuumbi Cave points. These same experiments also found that hinge termination, step terminating and tip crushing were also common occurrences for points used as arrow heads, with snap fractures occurring less frequently (Bradfield and Lombard 2011;Pargeter and Bradfield 2012;Bradfield and Brand 2015).…”
Section: Methodsmentioning
confidence: 99%